Exploring the Effects of Action Observation Therapy on Swallowing Disorders in Stroke: A Functional Connectivity–Based fMRI Study - Xuting Chen; Xiaolin Sun; Fang Shen; Zhongli Wang; Meihong Zhu; Jianming Fu; Yunhai Yao; Jie Wang; Linhua Tao; Lianjie Ma; Ming Zeng; Xudong Gu (Neural Plasticity)
Trial Registration: Chinese Clinical Trial Registry: ChiCTR1900021849